A monomer-dimer switch modulates the activity of plant adenosine kinase - Kopečný, David Jaroslav; Vigouroux, Armelle; Bělíček, Jakub; Kopečná, Martina; Končitíková, Radka; Friedecká, Jaroslava; Mik, Václav; Supíková, Klára; Humplík, Jan František; Le Berre, Marine; Plancqueel, Stephan; Strnad, Miroslav; et al. (Journal of experimental botany, 2025)
Adenosine undergoes ATP-dependent phosphorylation catalyzed by adenosine kinase (ADK). In plants, ADK also phosphorylates cytokinin ribosides, transport forms of the hormone. Here, we investigated the substrate preferences, oligomeric states, and structures of ADKs from moss (Physcomitrella patens) and maize (Zea mays) alongside metabolomic and phenotypic analyses. We showed that dexamethasone-inducible ZmADK overexpressor lines in Arabidopsis can benefit from a higher number of lateral roots and larger root areas under nitrogen starvation. We discovered that maize and moss enzymes can form dimers upon increasing protein concentration, setting them apart from the monomeric human and protozoal ADKs. Structural and kinetic analyses revealed a catalytically inactive unique dimer. Within the dimer, both active sites are mutually blocked. The activity of moss ADKs, exhibiting a higher propensity to dimerize, was 10-fold lower compared with maize ADKs. Two monomeric structures in a ternary complex highlight the characteristic transition from an open to a closed state upon substrate binding. This suggests that the oligomeric state switch can modulate the activity of moss ADKs and probably other plant ADKs. Moreover, dimer association represents a novel negative feedback mechanism, helping to maintain steady levels of adenosine and AMP.
Keywords: Zea mays; Protein Multimerization; purine; Bryopsida; Substrate Specificity; cytokinin; SnRK; adenosinkinasa; Adenosine kinase; kukuřice setá; overexpression; mechy; Arabidopsis; Physcomitrella patens; riboside; rostlinné proteiny; substrátová specifita; Plant Proteins; crystal structure; Adenosine Kinase; multimerizace proteinu